2020
DOI: 10.1017/s1049023x20001211
|View full text |Cite
|
Sign up to set email alerts
|

The National Emergency Medical Service Role During the COVID-19 Pandemic in Sierra Leone

Abstract: This report describes the main adaptive and transformative changes adopted by the brand-new National Emergency Medical Service (NEMS) to face the novel coronavirus disease 2019 (COVID-19) in Sierra Leone, including ambulance re-distribution, improvements in communication flow, implementation of ad-hoc procedures and trainings, and budget re-allocation. In a time-span of four months, 1,170 COVID-19 cases have been handled by the NEMS through a parallel referral system, while efforts have been made to manage the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 3 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Specific ambulances were dedicated solely for COVID-19 and the rest of the fleet maintained for essential health services. 25 Rapid expansion of COVID-19 treatment beds was achieved by converting existing hospital spaces into safe treatment and isolation centres, using pre-existing infrastructure and staff and modelled on a previous Ebola response model. 26 The response also differed from the Ebola response in that COVID-19 treatment centres were all located at government hospitals, as opposed to temporary Non Governmental Organisations (NGO) separate facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific ambulances were dedicated solely for COVID-19 and the rest of the fleet maintained for essential health services. 25 Rapid expansion of COVID-19 treatment beds was achieved by converting existing hospital spaces into safe treatment and isolation centres, using pre-existing infrastructure and staff and modelled on a previous Ebola response model. 26 The response also differed from the Ebola response in that COVID-19 treatment centres were all located at government hospitals, as opposed to temporary Non Governmental Organisations (NGO) separate facilities.…”
Section: Discussionmentioning
confidence: 99%
“…35 This could explain why adult medical and surgical admissions that require more out of pocket expenditure saw reductions, while services provided under the Free Healthcare Initiative 19 such as caesarean deliveries were resilient. Furthermore, as the National Emergency Medical Service ambulance system 25 is primarily intended for paediatric and maternal cases, which were unaffected from Q1 to Q2, it is possible that the protective effect of the free prehospital transport system maintained access for these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Case definition-based screening at the front gate of hospitals with linkage to hospital isolation units, provided further delineation between COVID-19 and non-COVID-19 care. Specific ambulances were dedicated solely for COVID-19 and the rest of the fleet maintained for essential health services(25). Rapid expansion of COVID-19 treatment beds was achieved by converting existing hospital spaces into safe treatment and isolation centres, using pre-existing infrastructure and staff and modelled on a previous Ebola response model(26).…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why adult medical and surgical admissions, that require more out of pocket expenditure, saw reductions whilst services provided under the Free Health Care Initiative(36) such as caesarean deliveries, were resilient. Furthermore, as the national ambulance service(25) is primarily intended for paediatric and maternal cases, which were unaffected from Q1-Q2, it is possible that the protective effect of free pre-hospital transport system maintained access for these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Located on the west coast of Africa, Sierra Leone, being one of the most undeveloped countries in the world, has a particularly vulnerable public health system ( 4 , 5 ). Even though Sierra Leone reacted quickly to the threat of COVID-19, implementing policies to contain the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ( 6 ), COVID-19 emerged as a serious public health challenge due to the weak health system, poverty, cultural norms, and limited medical resources ( 7 , 8 ) [e.g., a single ventilator was available for the whole population of Sierra Leone in the initial stage of the COVID-19 pandemic ( 1 )], which led to significant health concerns and socioeconomic issues. A related study showed that people lost their jobs and had difficulty providing food for their families as a consequence of COVID-19 lockdowns ( 1 ).…”
Section: Introductionmentioning
confidence: 99%